Knowledge, attitude and practices on dental caries and periodontal diseases of the health sciences students of the University of the Philippines Manila - Kalaw, Angela Vida T.
Oral health cannot be separated from one's health. As future healthcare professionals, it is every UP Manila health science student?s responsibility to provide holistic care to his or her patients. To be able to deliver holistic care, one should have knowledge on all aspects pertaining to health and this includes oral health.